(untitled) - Manzocchi, Stefano (New York, N.Y., 2003)
In this volume, well-known scholars examine the challenges facing the EU at the start of the Eastern enlargement, whose first wave should be decided at the end of 2002 and implementation in 2004-2006.
Keywords: International economic integration,Europe, Eastern,Europe, Central,Europe; Economic integration,Economic integration,Economic integration